Electrochemical Performance of Solid Oxide Cell Oxygen Electrodes Under Pressurization. (2nd June 2015) - Hughes, Gareth; Railsback, Justin; Butts, Danielle; Barnett, Scott A
Abstract : The solid oxide cell (SOC) composite oxygen electrodes (La0.8 Sr0.2 )0.98 MnO3-δ - Zr0.84 Y0.16 O2-γ (LSM-YSZ) and La0.6 Sr0.4 Fe0.8 Co0.2 O3-d (LSCF) - Ce0.8 Gd0.2 O1.95 (LSCF-GDC) were studied at oxygen partial pressure pO2 from 0.1 to 10 atm by impedance spectroscopy. Two primary responses were observed in the impedance spectra, which were fit using an equivalent circuit model with two RQ elements. A higher frequency response observed at 10 3 Hz varied as pO2 -0.25 . A lower frequency response observed at 10 to 100 Hz varied as pO2 -0.15 . Total electrode resistances decreased with increasing pO2 following a pO2 -0.17 dependence for LSM-YSZ and a pO2 -0.20 dependence for LSCF-GDC. Overall, the area-specific resistance of these SOC oxygen electrodes is reduced by a factor of 2 by increasing oxygen pressure from a nominal 0.2 atm (air) to 10 atm, thereby improving pressurized SOC performance.